Addendum: Measurement of charged particle yields from PMMA irradiated by a 220 MeV/u 12C beam. (19th October 2017) - Mattei, I; Battistoni, G; Collini, F; De Lucia, E; Durante, M; Fiore, S; La Tessa, C; Mancini-Terracciano, C; Marafini, M; Mirabelli, R; Muraro, S; Paramatti, R; et al.
Abstract: In this paper we report the re-analysis of the data published in Piersanti et al (2014 Phys. Med. Biol .59 1857) documenting the charged secondary particles production induced by the interaction of a 220 MeV/u 12 C ion beam impinging on a polymethyl methacrylate (PMMA) target, measured in 2012 at the GSI facility in Darmstadt (Germany). This re-analysis takes into account the inhomogeneous light response of the LYSO crystal in the experimental setup measured in a subsequent experiment (2014) performed in the Heidelberg Ion-Beam Therapy Center. A better description of the detector and re-calculation of the geometrical efficiencies have been implemented as well, based on an improved approach that accounts also for the energy dependence of the emission spectrum. The new analysis has little effect on the total secondary charged flux, but has an impact on the production yield and emission velocity distributions of the different particle species (protons, deuterons and tritons) at different angles with respect to the beam direction ( 60 ∘ and 90 ∘ ). All these observables indeed depend on the particle identification algorithms and hence on the LYSO detector energy response. The results of the data re-analysis presented here are intended to supersede and replace the results published in Piersanti et al (2014 Phys. Med. Biol .59 1857).